2019
DOI: 10.1186/s12866-019-1530-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Mycobacterium bovis genetic richness suggests that inwards cattle movements are a more important source of infection in beef herds than in dairy herds

Abstract: Background We used genetic Multi-Locus VNTR Analysis (MLVA) data gathered from surveillance efforts to better understand the ongoing bovine tuberculosis (bTB) epidemic in Northern Irish cattle herds. We modelled the factors associated with Mycobacterium bovis MLVA genotype richness at three analytical scales; breakdown level, herd level, and patch level, and compared the results between dairy and non-dairy production types. Results In 83% of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
0
18
1
Order By: Relevance
“…The MLVA genotype richness variable exhibited the strongest association with breakdown duration, both regarding effect size and in contribution to model fit. Previous work found that in a small number of herds, likely to be beef fattening enterprises, MLVA genotype accumulation was associated with the inwards purchase of cattle from over a wide geographical extent (Milne et al, 2019b). Despite this, we did not find that the number of inwards movements prior to breakdown was a particularly important predictor of breakdown length, e.g., (Reilly & Courtenay, 2007).…”
Section: Discussioncontrasting
confidence: 91%
“…The MLVA genotype richness variable exhibited the strongest association with breakdown duration, both regarding effect size and in contribution to model fit. Previous work found that in a small number of herds, likely to be beef fattening enterprises, MLVA genotype accumulation was associated with the inwards purchase of cattle from over a wide geographical extent (Milne et al, 2019b). Despite this, we did not find that the number of inwards movements prior to breakdown was a particularly important predictor of breakdown length, e.g., (Reilly & Courtenay, 2007).…”
Section: Discussioncontrasting
confidence: 91%
“…Herd history has been associated with breakdown length in previous studies outside of Ireland, though metrics of TB history were not always analogous to what was done in the present study [ 10 , 15 ]. A history of TB in a herd was associated with large (>13 reactors) bTB breakdowns, relative to small (2–4 reactors) in a case-control study in Ireland [ 30 ]. Interestingly, recent work suggested that that previous breakdown size was not associated with recurrence risk in Ireland [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was greater similarity when looking at the likelihood of RTA badgers and herds with milk licenses sharing MLVA types (decrease of 7% per km) compared to RTA badgers and herds without milk licenses (decrease of 11% per km). Whilst this difference is small, it suggests greater between-herd homogeneity in the M. bovis population in herds with milk licenses, compared to herds without, possibly due to inwards movements driving accumulations of within-herd MLVA type diversity in non-dairy herds [25].…”
Section: Discussionmentioning
confidence: 91%
“…Animal-level MLVA profiles of isolates were associated with anonymised breakdown-level data made available from the Animal and Plant Health Information System database (APHIS) [51], administered by the Department of Agriculture, Environment and Rural Affairs (DAERA). This enabled the determination of the number of M. bovis MLVA types present in each confirmed bTB breakdown; this dataset has been described in full elsewhere [25]. Additional relevant epidemiological variables included in these data were the breakdown start and end dates, presence of a milk license (dairy herds) or no milk license (non-dairy herds), herd size at the time of bTB breakdown, the number of inwards and outwards cattle movements in the year before breakdown, and the herd DVO.…”
Section: Cattle Datamentioning
confidence: 99%
See 1 more Smart Citation